Training and Mentoring on the Utilization of Education Reports in Preparing Teachers’ Work Result Plans at SMP Negeri 20 Lebong - Asmi Astuti; Yesi Susilawati; Atik Maryanti; Apriza Fitriani; Merri Sri Hartati; Hilyati Milla (Galuh International Journal of Community Service and Development, 2025)
This community service activity was conducted through an In-House Training (IHT) program aimed at addressing teachers' limited competence in using the Education Report as a data source for planning the Teacher Work Result Plan (RHK) at SMP Negeri 20 Lebong, Lebong Regency. The program involved teachers as the main participants and was implemented using a participatory and practice-based approach. The stages of the activity included problem identification, material delivery, group discussions, hands-on practice in analyzing Education Report data, and evaluation. The Education Report provided by the Ministry of Education, Culture, Research, and Technology was used as the primary reference for data-based planning. The results of the activity showed an increase in teachers' understanding and skills in interpreting educational data and formulating more targeted and evidence-based work plans. In addition, the program fostered collaborative and reflective practices among teachers in improving learning quality. This activity demonstrates that structured and sustainable training programs are essential to support data-driven educational planning and continuous improvement in schools.